Practical CBT : using functional analysis and standardised homework in everyday therapy - Bakker, Gary. (Bowen Hills, QLD : Australian Academic Press, 2008)
"It is the clinician's task to take what they know works and to tailor it to the person seeking their help. Successfully 'selling' this therapeutic model to the client relies on clearly explaining what is happening and reinforcing session achievements with effective change-directed homework. 'Practical CBT' is designed for a range of mental health professionals who have a thorough grounding in cognitive7F 13behaviour therapy and use it day-to-day in their practice. The book provides explicit assessment-to-treatment pathways with links to over 45 tried and tested ready-to-use homework scripts covering a range of common therapy issues including self-monitoring, self-esteem, decision making, depression, anxiety, sleep, and anger. The author is a highly experienced clinician with a firm adherence to the scientist-practitioner model and the use of evidence-based protocols."--Publisher's website.
Homework 25. Overwhelming sensory experiences -- Homework 26. Options when suicidal -- Homework 27. Graze foods -- Sleep -- Homework 28. Sleep hygiene -- Homework 29. Dream antidotes -- Anxiety management -- Homework 30. Worry questions -- Homework 31. Allocating worry time -- Homework 32. Relaxation session -- Homework 33. Mini-relaxers -- Homework 34. Subjective Units of Distress (SUDS) of 7 -- Homework 35. Reasonable versus unreasonable worries listing -- Homework 36. Thought-stopping -- Homework 37. Social phobia self-statements -- Homework 38. Over-breating experiment -- Homework 39. Caffeine reduction -- Anger management -- Homework 40. Angry self-talk -- Homework 41. Time-outs -- Situational factors -- Homework 42. Life change units -- Homework 43. Reasons to change -- Section Four. Scripts -- Script 1. Self-efficacy, self-esteem restoration -- Script 2. Introducting the CBT model -- Script 3. Individualised PMCs -- Script 4. Common or expected prognosis -- Script 5. Not just 'talk therapy' -- Script 6. Education about normal anxiety, grief and trauma reactions -- References.
Bibliography: p. 161-168.
Keywords: Cognitive therapy -- Handbooks, manuals, etc; Behavior modification -- Handbooks, manuals, etc; Behavioral assessment